(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article analyzes the terminology of Uzbek official business papers. The author studies the importance of terms in documents and business papers in the fields of linguistics, law and management. The article emphasizes that the documents are effective and understandable through the clear and direct use of terms. The development and problems of these terms in the Uzbek language are also covered.